Service-Oriented Architecture Initiatives with Information Quality: Exploring the Issues - Sulong, Muhammad Suhaizan; Koronios, Andy; Gao, Jing; Abdul-Aziz, Azlianor (2012)
The implementation of service-oriented architecture (SOA) initiatives can help a business to leverage technology and to make it more agile and flexible to respond to rapidly changing requirements. However, enterprises cannot fully exploit its benefits, if bad information is delivered that is worthless to customers, suppliers and partners. In this context, there is a need for quality information management to build reliable SOA-based systems from the beginning. Organisations – whether engaged in work-in-progress or at the beginning of SOA initiatives – need to ensure every business process works correctly and according to business needs and requirements, by considering information quality in their initial plans. This paper reports case study research undertaken in seven organisations via semi-structured interviews. It highlights a number of information quality related issues that they encountered during implementation of their SOA initiatives, provides the reasons behind these issues and suggests possible guidelines. Consequently, dimensions of information quality associated with the issues are determined for the organisations’ future reference for quality SOA initiatives.